2010
DOI: 10.1186/1472-6963-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of human papillomavirus vaccination for prevention of cervical cancer in Taiwan

Abstract: BackgroundHuman papillomavirus (HPV) infection has been shown to be a major risk factor for cervical cancer. Vaccines against HPV-16 and HPV-18 are highly effective in preventing type-specific HPV infections and related cervical lesions. There is, however, limited data available describing the health and economic impacts of HPV vaccination in Taiwan. The objective of this study was to assess the cost-effectiveness of prophylactic HPV vaccination for the prevention of cervical cancer in Taiwan.MethodsWe develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 59 publications
5
12
0
2
Order By: Relevance
“…This is similar to a recent study in Taiwan which showed the cost-effectiveness of universal vaccination of adolescent girls [51]. …”
Section: Discussionsupporting
confidence: 91%
“…This is similar to a recent study in Taiwan which showed the cost-effectiveness of universal vaccination of adolescent girls [51]. …”
Section: Discussionsupporting
confidence: 91%
“…Inconsistent or negligible efficacy was observed for women aged 21 to 25 years, likely due to a higher proportion of women with prevalent infections at baseline. This is in line with analyses suggesting reduced or negligible cost-effectiveness of vaccination programs in women aged 21 years and above (36,44). For women aged 18 to 25 years, unfortunately neither the models nor our data are conclusive.…”
Section: Discussionsupporting
confidence: 71%
“…Another cost-effectiveness study comparing HPV vaccination with no vaccination for Taiwan estimated the incremental cost-effectiveness at US $13,674 per QALY. Although this ratio was slightly higher than the ratio estimated by Suárez et al (partly because of differences in the perspective and the discount rate applied for outcomes in both studies, 3% in the Liu et al study and 1.5% in the Suarez study), it was also concluded that HPV vaccination would result in a favorable cost-effectiveness ratio [22]. Therefore, we may accept that the introduction of HPV vaccination can be cost-effective in Taiwan.…”
Section: Introductionmentioning
confidence: 71%